2013
DOI: 10.1016/j.ajo.2013.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Predictability of Intraocular Lens Power Calculation Formulae in Infantile Eyes With Unilateral Congenital Cataract: Results from the Infant Aphakia Treatment Study

Abstract: PURPOSE To compare accuracy of intraocular lens (IOL) power calculation formulae in infantile eyes with primary IOL implantation. DESIGN Comparative case series. METHODS The Hoffer Q, Holladay 1, Holladay 2, Sanders-Retzlaff-Kraff (SRK) II, and Sanders-Retzlaff-Kraff theoretic (SRK/T) formulae were used to calculate predicted postoperative refraction for eyes that received primary IOL implantation in the Infant Aphakia Treatment Study. The protocol targeted postoperative hyperopia of +6.0 or +8.0 diopters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 32 publications
2
47
0
1
Order By: Relevance
“…Andreo et al 4 reported that there was minimal difference between SRK/T, SRK II, Holladay 1, and Hoffer Q formulae in terms of their predictive accuracy in short, medium, and long eyes. Vanderveen et al 12 reported results from 43 eyes of infants, with a mean age of 2.5 months and ALo20 mm in most eyes. In this prospective, randomized multicenter trial, they reported that both SRK/T and Holladay 1 formulae worked equally well in terms of median prediction errors.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Andreo et al 4 reported that there was minimal difference between SRK/T, SRK II, Holladay 1, and Hoffer Q formulae in terms of their predictive accuracy in short, medium, and long eyes. Vanderveen et al 12 reported results from 43 eyes of infants, with a mean age of 2.5 months and ALo20 mm in most eyes. In this prospective, randomized multicenter trial, they reported that both SRK/T and Holladay 1 formulae worked equally well in terms of median prediction errors.…”
Section: Discussionmentioning
confidence: 99%
“…Further, they also reported that age, AL, and K values did not influence predictive accuracy, except for the Holladay and Hoffer Q formulae that were influenced by AL. On the other hand, several authors 5,12 reported that a shorter AL had a significant bearing on the predictive accuracy of the IOL calculation formula. Although mean PE tells us about the direction of miscalculation, the APE is a useful measure to compare overall predictive accuracy of the different formulae.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations